Penyelesaian Kasus Kecelakaan Lalulintas Secara Damai (Restorative Justice) di Kota Kupang - Anggelina Ikun Sally; Reny Rebeka Masu; Orpa Ganefo Manuain (Pusat Riset dan Inovasi Nasional, 2025)
Most people do not know the legal basis for resolving traffic accidents that result in death through restorative justice (peaceful, family). Such a wrong public perception will cause great harm to the government's efforts to develop in the legal field, among other things, it can raise confusing questions. This study is a contribution of researchers' thoughts to participate in solving one of the legal problems that have long occurred in society. The research used is juridical-sociological or empirical research with a legal research approach. This research is an in-depth interview. The data collected are verbal and nonverbal. The conversation is recorded in a notebook or recorded with a tape recorder. The data is processed, analyzed and interpreted in a juridical-descriptive manner to explain or describe the data obtained by providing a logical interpretation and confirmed by the opinions of experts. The results of the study indicate that the causal factors or reasons for peaceful resolution or restorative justice of traffic accident cases resulting in fatalities at the Kupang City Police Resort are public legal awareness, public tendency to prioritize peace and family, and police discretionary authority. The practice of restorative justice resolution of traffic accident cases resulting in fatalities is carried out through the stages of the Approach Stage, Mediation Stage, Agreement Making Stage, Agreement Implementation Stage, and Completion and Case Closed Management.